2009
DOI: 10.1111/j.1365-2621.2008.01868.x
|View full text |Cite
|
Sign up to set email alerts
|

The rheological properties of ketchup as a function of different hydrocolloids and temperature

Abstract: The flow properties of ketchup were assessed upon addition of commonly used food thickeners: guar, xanthan and CMC gum at three different concentrations (0.5%, 0.75% and 1%) and four temperatures (25, 35, 45 and 55°C). The ketchup without supplementation served as a control. All ketchup formulations exhibited non-Newtonian, pseudoplastic behaviour at all temperatures and hydrocolloid levels. The Powerlaw and Herschel-Buckley model were successfully applied to fit the shear stress versus shear rate data. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
91
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 30 publications
11
91
0
1
Order By: Relevance
“…The significant influence of temperature on the viscosity of bio-materials was reported by previous researchers (Sharoba et al, 2005;Ibarz et al, 1996). Koocheki et al (2009) observed a decline in flow behavior index (n) with temperature of tomato ketchup, which indicates higher pseudoplasticity at higher temperature. Temperature has limited influence on the apparent viscosity of considerably pseudoplastic products (Sharoba et al, 2005).…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 86%
“…The significant influence of temperature on the viscosity of bio-materials was reported by previous researchers (Sharoba et al, 2005;Ibarz et al, 1996). Koocheki et al (2009) observed a decline in flow behavior index (n) with temperature of tomato ketchup, which indicates higher pseudoplasticity at higher temperature. Temperature has limited influence on the apparent viscosity of considerably pseudoplastic products (Sharoba et al, 2005).…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 86%
“…Consistency index and apparent viscosity increase with the addition of all hydrocolloids, but the increase is highest with the addition of guar and LBG, followed by xanthan and tragacanth and the least with CMC. Koocheki et al (2009) found that though guar gum produced higher apparent viscosity in tomato ketchup as compared to xanthan and CMC, the yield stress is higher for ketchups with xanthan and CMC but lower after addition of guar gum.…”
Section: Thickening Agentsmentioning
confidence: 98%
“…The important property of guar gum is its resistance to breakdown Koocheki et al 2009 under low pH conditions present in beverages. Guar gum is soluble in cold water which makes it easy to use in beverage processing plants.…”
Section: Beveragesmentioning
confidence: 99%